2016
DOI: 10.1080/10790268.2016.1177269
|View full text |Cite
|
Sign up to set email alerts
|

Does attendance in SCI education courses impact health outcomes in acute rehabilitation?

Abstract: Results of the study are mixed. Multiple factors appear to impact the success of education interventions. Future research is needed to clarify the best approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Consistent with other studies, rehabilitation following SCI was perceived as a phase in which every single activity, combined with medical management, is exhausting and has an effect on individuals' readiness to learn [15]. Physical and psychological stressors experienced by SCI survivors during early rehabilitation represent barriers to their participation in educational programmes [13].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Consistent with other studies, rehabilitation following SCI was perceived as a phase in which every single activity, combined with medical management, is exhausting and has an effect on individuals' readiness to learn [15]. Physical and psychological stressors experienced by SCI survivors during early rehabilitation represent barriers to their participation in educational programmes [13].…”
Section: Discussionmentioning
confidence: 69%
“…Thus, practical, and cost-effective strategies that can be implemented in educational programmes early in the rehabilitation process need to be identified [ 13 ]. Recent studies showed conflicting evidence on the effectiveness of available educational programmes in improving patients’ problem-solving skills, their knowledge of the injury, self-management skills, and QoL [ 14 , 15 ]. Several clinical and environmental factors have been associated with successful educational programmes in early rehabilitation; most are related to the perspectives that those with SCI have towards health, their access to such programmes and their engagement in the rehabilitation process [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of knowledge on SHCs is a concern because education on SHCs is fundamental to the prevention of diseases and a key focus area in achieving Sustainable Developmental Goal 3 through strengthening health literacy (World Health Organization 2017 ). Although knowledge on SHC does not necessarily mean positive behaviour change (Evardone et al 2018 ), efforts to educate patients on health and secondary complications throughout their journey are essential. On the contrary, patients can forget what they were taught.…”
Section: Discussionmentioning
confidence: 99%